Zebrafish as a Model for Fetal Alcohol Spectrum Disorders - Alsakran, Amena; Kudoh, Tetsuhiro (Frontiers in Pharmacology, 2021)
In this review, we will discuss zebrafish as a model for studying mechansisms of human fetal alcohol spectrum disorders (FASDs). We will overview the studies on FASDs so far and will discuss with specific focus on the mechanisms by which alcohol alter cell migration during early embryogenesis including blastula, gastrula and organogenesis stages which later cause morphological defects in the brain and other tissues. FASDs are caused by an elevated alcohol level in the pregnant mother’s body. The symptoms of FASDs include microcephaly, holoprosencephaly, craniofacial abnormalities, cardiac defects with birth defect in severe cases and with milder cases the symptoms leading to developmental and learning disabilities. The transparent zebrafish embryo offers an ideal model system to investigate the genetic, cellular and organismal response to alcohol. In the zebrafish, the effects of alcohol were observed in many places during embryo development from stem cell gene expression at blastula/gastrula stage, gastrulation cell movement, morphogenesis of the central nervous system and neuronal development. The data revealed that ethanol suppresses convergence, extension and epiboly cell movement at gastrula stage and cause the failure of normal neural plate formation. Subsequently other cell movements including neurulation, eye filed morphogenesis and neural crest migration are also suppressed, leading to malformation of the brain and spinal cord, including microcephaly, cyclopia and spinal bifida and craniofacial abnormalities. The testing cell migration in zebrafish would provide convenient biomarkers for the toxicity of alcohol and other related chemicals and investigate the molecular link between the target signaling pathways and following brain development.